Bermudagrass Stem Maggot—A New Pest in Florida - Ann Blount; Tim Wilson; Jay Ferrell; Russ Mizell; Jonael Bosques (EDIS)
Bermudagrass is a dominant hay crop in Florida. Now, hay producers are facing a new emerging pest problem in bermudagrass and stargrass production fields. The bermudagrass stem maggot is a new exotic invasive fly. It was first discovered damaging bermudagrass pasture and hay fields in Georgia. The identification of the fly was the first record of this species in North America, and it has the potential to become a serious pest of bermudagrass and stargrass in Florida. This 2-page fact sheet was written by Ann Blount, Tim Wilson, Jay Ferrell, Russ Mizell, and Jonael Bosques, and published by the UF Department of Agronomy, June 2014.